Learners’ Engagement with Digital Literature in EFL Contexts: A Systematic Literature Review from a Multimodal Perspective - David Togi Hutahaean; Rudi Hartono; Yuliati (Journal of Education and Teaching Learning, 2026)
This systematic literature review aims to examine how previous studies have investigated learners’ engagement with digital literature in EFL contexts from a multimodal perspective. Existing research has widely discussed digital storytelling, digital multimodal composing, multimodal literacy, and educational technology in English language learning; however, the relationship between digital literature, learner engagement, and multimodal meaning-making remains fragmented. To address this gap, this study reviewed 12 preliminary articles published between 2016 and 2026 from relevant international and Indonesian academic sources, using a systematic review procedure informed by PRISMA 2020 and Zawacki-Richter et al.’s approach to educational systematic reviews. The analysis focused on research demographics, forms of digital literature, dimensions of learner engagement, multimodal elements, benefits, challenges, and research gaps. The findings show that digital storytelling and digital multimodal composing dominate the literature, while other digital literary forms such as interactive fiction, e-poetry, hypertext narratives, fanfiction, and social media-based literature remain underexplored. The review contributes by proposing that EFL learners’ engagement with digital literature should be understood as behavioral, emotional, cognitive, and multimodal participation in meaning-making